2006
DOI: 10.1677/jme.1.01964
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dihydrotestosterone on skeletal muscle transcriptome in mice measured by serial analysis of gene expression

Abstract: In order to characterize the action of androgen in skeletal muscle, we have investigated the effects of castration (GDX) and dihydrotestosterone (DHT) on global gene expression in mice. The serial analysis of gene expression method was performed in the muscle of male mice in six experimental groups: intact, GDX and GDX+DHT injection 1, 3, 6 or 24 h before they were killed. A total of 780 822 sequenced tags quantified the expression level of 80 142 tag species. Thirteen and seventy-nine transcripts were differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 70 publications
2
45
0
Order By: Relevance
“…We have already reported that DHT injection into GDX male mice immediately induces transcripts related to power generation, protein synthesis, mitochondrial function, and satellite cells/myoblasts proliferation, in which only transcripts related to protein synthesis have been repressed at late time point (Yoshioka et al 2006). In the present study, DHT injection into female GDX mice increased contractility as well as glucose transport and glycogenolysis/glycolysis at the transcriptional level.…”
Section: Gender Difference In Dht Actionssupporting
confidence: 67%
See 4 more Smart Citations
“…We have already reported that DHT injection into GDX male mice immediately induces transcripts related to power generation, protein synthesis, mitochondrial function, and satellite cells/myoblasts proliferation, in which only transcripts related to protein synthesis have been repressed at late time point (Yoshioka et al 2006). In the present study, DHT injection into female GDX mice increased contractility as well as glucose transport and glycogenolysis/glycolysis at the transcriptional level.…”
Section: Gender Difference In Dht Actionssupporting
confidence: 67%
“…The common functional regulation by DHT in the female mice of the present study and male mice of our previous studies (Yoshioka et al 2006) was an induction of transcripts involved in muscle relaxation at early time points, although male mice have shown concomitant increase in transcripts related to muscle contraction. The main difference between male and female mice in response to DHT injection was seen in transcripts related to mitochondrial function.…”
Section: Gender Difference In Dht Actionssupporting
confidence: 63%
See 3 more Smart Citations